ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN DIKLAT KETERAMPILAN PELAUT DI PIP SEMARANG - Prapti Utami (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The findings on empirical phenomena are related to the fluctuation of the Sailors Skill Training participants and are still below the target of the assigned participants. Searches of previous studies found that testing on the effect of service quality on customer loyalty still showed inconclusive results. Based on the empirical and theoretical phenomena that have been mapped, this research is intended to examine about customer loyalty.The research model involves variable quality of service, customer satisfaction and loyalty. The data were obtained through interview with questionnaires to participants of Sailor skill training at Polytechnic Science of Semarang Sailing which amounted to 95 people. The data obtained are then analyzed by Double Regression Test. The result of multiple regression test showed that service quality proved to have a positive significant effect on satisfaction, satisfaction proved to have a significant positive effect on customer loyalty and service quality proved to have a significant positive effect on customer loyalty.